Coupling coordination and obstacle factors of cultivated land system resilience and new urbanization - Weijuan Li; Weijuan Li; Jinyong Guo (Frontiers in Sustainable Food Systems)
The global food crisis is becoming increasingly severe, highlighting the need to enhance cultivated land system resilience to improve utilization efficiency and strengthen its ability to withstand external shocks, ensuring food security. This study examines 13 major grain-producing areas in China to clarify the coupling coordination mechanism between cultivated land system resilience and new urbanization. An evaluation system is constructed, and development levels are assessed using the entropy method, the coupling coordination degree model, and the obstacle degree model. The main results are as follows: (1) Cultivated land system resilience and new urbanization in China’s major grain-producing areas have exhibited a steady upward trend. (2) The coupling coordination degree has increased from 0.5512 to 0.6788. (3) The primary obstacle factors at the criterion layer are output resilience, scale resilience, and land urbanization. To strengthen the coordination between cultivated land system resilience and new urbanization, policies should be reinforced, the efficiency of cultivated land utilization and agricultural labor productivity should be improved, urbanization planning should be optimized, and regional linkages should be enhanced.